Effects of Lactobacillus plantarum (L) and molasses (M) on nutrient composition, aerobic stability, and microflora of alfalfa silage in sandy grasslands - Peng, Wen; Zhang, Liyuan; Wei, Manlin; Wu, Baiyila; Xiao, Ming; Zhang, Runze; Ju, Ji; Dong, Chenyang; Du, Liu; Zheng, Yongjie; Bao, Meili; Bao, Hailin; et al. (Frontiers in Microbiology, 2024)
The objective of this experiment was to investigate the effects of Lactobacillus plantarum and molasses on the nutrient composition, fermentation quality, bacterial count, aerobic stability, and microflora of alfalfa silage in sandy grasslands. The experimental treatments included control (CK), 10 6 CFU/g Lactobacillus plantarum (L), 5% molasses (M), and 10 6 CFU/g Lactobacillus plantarum + 5% molasses (LM). The nutrient composition, fermentation quality, bacterial count, aerobic stability, and microflora were determined after 14 days and 56 days of ensiling, respectively. The results showed that the addition of L, M, and LM reduced dry matter loss (DM), neutral detergent fiber (NDF), and acid detergent fiber (ADF) content, and increased water-soluble carbohydrates (WSC) and ether extract (EE) content, compared to the CK group. Meanwhile, more lactic acid (LA) and accelerated fermentation were observed, causing the pH value to drop below 4.5 in the L, M, and LM groups after 56 days of ensiling. The addition of L, M, and LM promoted lactic acid bacteria (LAB), and inhibited yeast. The addition of L significantly increased the content of acetic acid (AA). In terms of microflora, the addition of L, M, and LM made Firmicutes become the dominant bacterial phylum earlier, while Lactobacillus, Weissella, and Pediococcus had a higher abundance. According to the result of Pearson's correlation, there is a very significant negative correlation between pH value and Lactobacillus (P < 0.01) and a very significant positive correlation between pH value and Lactococcus, Enterobacter, Enterococcus, and Leuconostoc (P < 0.01), which may be inhibited by Lactobacillus under the decreased pH value. The results of the prediction of microbial genes indicated that the addition of M could enhance the carbohydrate metabolism and membrane transport metabolism, which may contribute to LA production by LAB metabolism. In general, L, M and LM all improved the fermentation quality and reduced the loss of nutrients to varying degrees, but considering the